Socio-Demographic Risk Factors for Severe Acute Malnutrition - Akther, Naznin; Azad, Md Tarek; Chowdhury, Tahmina Jahan; Hussain, Md Muazzem; Akter, Forida; Talukder, Aloka Nanda (Jalalabad Medical Journal, 2025)
Malnutrition is one of the leading causes of morbidity and mortality in under-five children in developing countries. Bangladesh being one of the developing countries, malnutrition is an important public health problem. This was a hospital-based case-control study conducted in the department of Paediatrics, Jalalabad Ragib-Rabeya Medical College Hospital, Sylhet during the period from July 2013 to June 2014 to see the socio-demographic risk factors for severe acute malnutrition among children under five. Forty-five severe acute malnourished children, aged 6 months to 5 years, with a weight-for-height Z score below -3 were enrolled in the case group. Controls were age and sex matched, well-nourished children with a weight-for-height Z score of -1 to <+2 who were admitted at the same time following the admission of the case due to other problems. Rural participants (p<0.001), undernourished mother (p=0.006), less-educated parents (p<0.001), lower monthly income (p=0.005), birth order 3 or more (p=0.017), family member 5 or higher (p=0.015), lack of exclusive breast feeding (p<0.001), and inappropriate weaning (p<0.001) significantly increased the risk of development of severe acute malnutrition. To reduce childhood malnutrition, due emphasis should be given to improve the socioeconomic status, parental education, knowledge and practice of parents on appropriate infant and child feeding practices. Jalalabad Med J 2022; 19 (2): 47-53